RANCANG BANGUN SISTEM INFORMASI PENERIMAAN DAN PENGELUARAN DANA KAS PADA PERUSAHAAN DENGAN SAK (STANDAR AKUNTANSI KEUANGAN) YANG MENGGUNAKAN MODEL WATERFALL - Rabiatul Adwiya (JTIK (Jurnal Teknik Informatika Kaputama), 2023)
Management of transactions such as cash receipts and disbursements at the company which are recorded in transaction notes which are then copied to Ms. Excel. To produce financial reports takes a long time, because the finance department must recapitulate one by one receipt and expenditure transactions to be used as cash receipts reports, cash disbursements reports, income statements, reports of changes in capital and balance sheets. Delays in the presentation of this report affect the decision-making process, especially those related to financial matters. In addition, there are often discrepancies or errors in the allocation of transactions by the finance department. The purpose of this research is to assist the company in managing data related to receipts and expenditures transactions to be faster and to produce financial reports quickly, on target and in accordance with Financial Accounting Standards (SAK). The model used in software development is the Waterfall model. The result of this research is to produce an accounting information system of cash receipts and disbursements providing processing of cash receipts and disbursements which are equipped with reports.